React projects : build 12 real-world applications from scratch using React, React Native, and React 360 - Derks, Roy (Packt Publishing, 2019)
React, an intuitive web frontend framework, extends its capabilities in building apps for mobile and VR. This book aims to help you in building React applications through a series of real-world projects increasing in complexity as you progress. With coverage on various modern React tooling, you will get a wholesome knowledge of React development.